A heteropolysaccharide purified from leaves of Ilex latifolia displaying immunomodulatory activity in vitro and in vivo. (1st October 2020) - Shi, Zhaoyu; An, Lijun; Zhang, Shaojie; Li, Zhengguo; Li, Yuhao; Cui, Jianlin; Zhang, Jie; Jin, Da-Qing; Tuerhong, Muhetaer; Abudukeremu, Munira; Xu, Jing; Guo, Yuanqiang
Highlights: A novel heteropolysaccharide ILP50-2 was purified from leaves of Ilex latifolia Thunb. The structure of ILP50-2 was established mainly through NMR, GC–MS and HPSEC-MALS. ILP50-2 mainly consisted of mannose, rhamnose, glucose, galactose, and arabinose with Mw of 1.49 × 10 5 g/mol. ILP50-2 showed significant immunomodulatory activities in vitro and in vivo . Abstract: A novel polysaccharide (ILP50-2) was extracted, isolated and purified from the leaves of Ilex latifolia Thunb. Its structure was characterized as a repeating unit consisting of α -L-Ara f -(1→, →3)- α -L-Ara f -(1→, →5)- α -L-Ara f -(1→, →3, 5)- α -L-Ara f -(1→, →2)- α -L-Rha p -(1→, →2, 4)- α -L-Rha p -(1→, β -D-Gal p -(1→, →4)- β -D-Gal p -(1→, →4)- β -D-Glc p -(1→, →6)- α -D-Man p -(1→, and →3, 6)- α -D-Gal p -(1→. The absolute molecular weight of ILP50-2 was 1.49 × 10 5 g/mol, which adapted a compact coil conformation in 0.1 M NaCl solution with Rz of 25.4 nm. Furthermore, ILP50-2 exhibited immunoregulatory activity, mainly through enhancing the phagocytosis ability of macrophages and prompting the release of nitric oxide (NO) and cytokines tumor necrosis factor- α (TNF- α ), interleukin-6 (IL-6), and interleukin-1 β (IL-1 β ). Simultaneously, ILP50-2 was found to significantly increase the release of ROS and NO in zebrafish embryos, showing immunoregulatory effects in vivo .